As configurações do futebol brasileiro: análise da trajetória de um treinador - Talamoni, Guilherme Augusto [UNESP]; Oliveira, Flávio Ismael da Silva [UNESP]; Hunger, Dagmar Aparecida Cynthia França [UNESP] (My University, 2013)
The present article is set to analyze the career of a soccer coach, highlighting information that may be assist in the discussion on graduating and professional actuation in Physical Education and Sports. The research, qualitative, used Life History as a method of data collection. To elucidate and articulate issues raised was used concepts from sociological theory of Norbert Elias. From the explicit path and the proposed configuration of Elias, we conclude that the figure of the trainer was formed as a result of interdependence established within the specific groups which took part, enriched by the academic.
The configurations of brazilian soccer: Trajectory analysis of a coach
Las configuraciones del fútbol brasileño: Análisis de la trayectoria de un entrenador
Keywords: Coach; Professional actuation; Soccer